Detection and Stability Evaluation of Coal Mine Goafs under Transmission Lines - Wang, Ning; Wang, Tianyu; Sun, Haoyue; Qi, Haochen (Journal of Progress in Civil Engineering, 2025)
To ensure the safety of transmission lines, this study conducts a systematic investigation and evaluation of concealed coal mine goafs along the route. The research begins with a detailed survey using the high-density resistivity method. Through the interpretation of inverted resistivity profiles, the spatial location, burial depth, and approximate scale of several water-filled goafs were successfully identified, with the results subsequently verified by borehole data. On this basis, combining geophysical findings with geotechnical analysis, a stability evaluation of the goaf sites was performed. The evaluation indicates that some goafs are in a sub-stable state, posing a potential threat to the surface transmission facilities. In response to the risks revealed by the evaluation, this paper further explores and proposes corresponding preventive treatment measures. This research provides an effective technical framework and engineering basis for the accurate detection of concealed goafs, scientific evaluation of their stability, and the formulation of treatment plans.